2002
DOI: 10.1080/1042819022386617
|View full text |Cite
|
Sign up to set email alerts
|

Agranular CD4+/CD56+ Cutaneous Neoplasm

Abstract: CD4+ CD56+ cutaneous neoplasm with hematological relapse is a rare malignant disease and has been described recently in the literature as blastic or agranular NK-cell leukemia/lymphoma. The origin of this neoplasm is uncertain. We describe a 75-year-old patient with a primary cutaneous neoplasm CD4+ CD56+ who evolved to leukemic phase despite standard lymphoma chemotherapy. Morphologically, the cells were undifferentiated without granules in the cytoplasm. The immunophenotype showed the expression of CD4, CD56… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In addition, 5 other studies reported a low CD33 expression in a least one case in their series of CD4 ϩ CD56 ϩ lineage-negative malignancies. 45,[47][48][49][50] Up-regulation of CD33 expression on leukemic pDCs in culture after maturation into potent APCs 17 also supports the idea that CD33 is expressed by pDCs during their differentiation process.One has also to consider the plasticity of DC differentiation. Canque and Gluckman 4 and Gluckman et al 51 have proposed that DCs may differentiate from many precursors (either immature or already committed to lymphoid or myeloid lineages).…”
mentioning
confidence: 59%
“…In addition, 5 other studies reported a low CD33 expression in a least one case in their series of CD4 ϩ CD56 ϩ lineage-negative malignancies. 45,[47][48][49][50] Up-regulation of CD33 expression on leukemic pDCs in culture after maturation into potent APCs 17 also supports the idea that CD33 is expressed by pDCs during their differentiation process.One has also to consider the plasticity of DC differentiation. Canque and Gluckman 4 and Gluckman et al 51 have proposed that DCs may differentiate from many precursors (either immature or already committed to lymphoid or myeloid lineages).…”
mentioning
confidence: 59%
“…The major difficulty with pDC and pDCL is that they may express shared markers with other lineages (Jacob et al, 2003), notably 'strong' markers used to calculate score (such as the EGIL score). CD33 was the most frequently reported myeloid marker (Gattei et al, 1990;Ginarte et al, 2000;Mhawech et al, 2000;Rakozy et al, 2001;Touahri et al, 2002;Karube et al, 2003;Kazakov et al, 2003;Bueno et al, 2004;Giagounidis et al, 2004;Garnache-Ottou et al, 2005a). We recently used functional assays to validate that both pDCL and normal pDC express CD33 at low levels (Garnache-Ottou et al, 2005a).…”
Section: Markers Expressed By Cells Of Plasmacytoid Dendritic Cell Lementioning
confidence: 99%